2007
DOI: 10.1029/2007jd008844
|View full text |Cite
|
Sign up to set email alerts
|

Water‐soluble species in the marine aerosol from the northern South China Sea: High chloride depletion related to air pollution

Abstract: [1] Dichotomous (PM 2.5 -10 and PM 2.5 modes) and size-resolved marine aerosols collected during the northeastern monsoon on two wintertime cruises in the subtropical South China Sea (SCS) were analyzed for water-soluble ions. During the sampling periods the study region was under the influence of strong pollution originating primarily from the Asian continent. Elevated levels of non-sea-salt sulfate and ammonium ions of up to 4.5 and 1.2 mg/m 3 , respectively, were observed, indicating that the SCS is now sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 52 publications
5
66
1
Order By: Relevance
“…Mixing between sea salt and oxalate is also observed (Kerminen et al 1998;Yang et al 2009). A number of studies have reported large variations in the magnitude of Cl-depletion (ranging from few percent to 100 %) over different oceanic regions (Graedel and Keene 1995;Song and Carmichael 1999;Maxwell-Meier et al 2004;Quinn and Bates 2005;Hsu et al 2007). This variability has been attributed to the complex interplay of several factors, including variable wind-field, turbulence in the vicinity of the sampling site and the influence of anthropogenic components.…”
Section: Sea Saltmentioning
confidence: 86%
See 1 more Smart Citation
“…Mixing between sea salt and oxalate is also observed (Kerminen et al 1998;Yang et al 2009). A number of studies have reported large variations in the magnitude of Cl-depletion (ranging from few percent to 100 %) over different oceanic regions (Graedel and Keene 1995;Song and Carmichael 1999;Maxwell-Meier et al 2004;Quinn and Bates 2005;Hsu et al 2007). This variability has been attributed to the complex interplay of several factors, including variable wind-field, turbulence in the vicinity of the sampling site and the influence of anthropogenic components.…”
Section: Sea Saltmentioning
confidence: 86%
“…The release of reactive chloride is considered to be an important intermediate in the oxidation reactions associated with the removal of light hydrocarbons and ozone in the marine atmosphere (Singh and Kasting 1988;Vogt et al 1996). The magnitude of Cl-depletion of marine aerosols has been demonstrated to usually increase with decreasing sea salt particle size (Mouri and Okada 1993;Kerminen et al 1998;Yao et al 2003;Hsu et al 2007). This reaction produces sea salt particles coated with sulphate and nitrate over Asian and Pacific areas (Matsumoto et al 2004;Matsuki et al 2005;Yang et al 2009) and in the Mediterranean region (Tursic et al 2006).…”
Section: Sea Saltmentioning
confidence: 99%
“…The East Asian region comprises of continental locations of south China, Mongolia, Korea, etc., where the anthropogenic aerosol concentrations were reported to be very high (e.g. Hsu et al, 2007;Sahu et al, 2009). However, as the source contribution from the Indian mainland increases from ∼0.05 to as high as 0.30, the spectral curvature of AOD changes to concave (bottom right panel of Fig.…”
Section: Cwt Analysis and Potential Source Regionsmentioning
confidence: 99%
“…The sampled rainwater was immediately filtered through a polycarbonate membrane with a pore size of 0.45 μm and a diameter of 47 mm (Nuclepore Track Etched Membranes, Whatman, Kent, UK) by using plastic filtration units (Nalgene Filterware 300-4100, Techmate, Milton Keynes, UK). An aliquot of filtered water was subjected to chemical analyses of ionic composition, including NH 4 + and NO 3 , with an ion chromatograph (Dionex ICS 90 and ICS 1500, Thermo Scientific Dionex, California, USA) (Hsu et al 2007). The collected rain volume was converted into the corresponding amount of precipitation by dividing it by the area (0.0919 m 2 ) of the receiving funnel.…”
Section: Methodsmentioning
confidence: 99%